Antibacterial potential of inulinase enzyme obtained from Nocardiopsis sp. - N Neha; Pitchiah Sivaperumal; Anitha Roy (Wolters Kluwer Medknow Publications, 2022)
The enriched nutritional and functional properties of inulinase with wide attention are considered commercial/industrial food enzymes. It can be produced by many microorganisms such as yeasts, fungi, and bacteria. Nocardiopsis is a genus under Actinomycetes, which has biotechnologically important microorganisms. This study aims to isolate and identify marine Actinomycetes Nocardiopsis species and to evaluate the antibacterial potential of the inulinase enzyme obtained from it. Marine actinobacteria (Nocardiopsis sp.) were isolated from sediment samples on YM agar. The isolate was identified by biochemical analysis of cell walls (amino acid and sugar). Enzyme screening assay was performed with temperature and pH influence in the production inulinase enzyme production. Antibacterial activity and minimal inhibitory activity of inulinase enzyme were performed with Staphylococcus, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Antimicrobial testing revealed that with higher concentrations of inulinase enzyme, the zone of inhibition of bacterial growth increased, and the minimum inhibitory concentration of inulinase enzyme that prevented the growth of bacteria was close to the standard tetracycline. Inulinase enzyme obtained from Nocardiopsis species shows good antibacterial activity against Staphylococcus aureus, K. pneumoniae, and P. aeruginosa in comparison to the standard, tetracycline.